Buccolingual inclination of posterior dentition in maxillary impacted canine patients using quadrant analysis - A cone-beam computed tomographic study - Tevhide Sokmen; Nuray Bagcı; Burcu Balos Tuncer (BMC, 2024)
Abstract Background To examine the buccolingual inclination of maxillary posterior teeth, curve of Wilson, and transversal dimensions in palatally impacted maxillary canine patients, compared to controls by cone-beam computed tomography (CBCT). Materials and methods Pre-treatment images of 22 bilateral, 32 unilateral impacted maxillary canine patients and 30 controls were included. All patients had palatally impacted canines, with no posterior cross-bite. Data were reclassified in quadrants according to the presence of impaction, as the impaction quadrant (right and left quadrants of 22 bilateral impacted cases, and quadrants presenting impaction of 32 unilateral cases, n = 76), unaffected quadrant (quadrant without impaction in 32 unilateral cases, n = 32) and the control quadrant (right and left quadrants of 30 controls, n = 60) to evaluate the buccolingual inclination angle, transversal width, and arch perimeter. Additionally, comparisons were made regarding curve of Wilson and total arch perimeter among bilateral and unilateral impaction groups with the control group. Statistical analysis was performed by one-way ANOVA and Kruskal Wallis tests. Tukey or Dunn tests were used for comparisons between groups in pairs. Results No significant difference was found for the buccolingual inclination of maxillary posterior teeth and curve of Wilson among groups. The buccolingual inclination of canines in the impaction quadrant was significantly lower than the other quadrants (p < 0.001). Basal bone width at the level of second premolars, and alveolar width at both premolars were significantly narrower in the impaction quadrant than in the unaffected quadrant (p < 0.05). Dental arch width at the level of first premolar was significantly decreased in the impaction quadrant compared to other quadrants (p < 0.05). Arch perimeter was significantly reduced in the impaction quadrant than in the unaffected quadrant (p < 0.05). Conclusion The presence of bilateral or unilateral palatally impacted maxillary canines did not effect the buccolingual inclination of posterior teeth, and curve of Wilson. Transverse discrepancy was evident in the impaction quadrant even in the absence of posterior cross-bite. Quadrant analysis was particularly useful in evaluating asymmetry for basal bone and alveolar bone widths in the premolar region in patients with unilateral palatally impacted maxillary canine patients.